Programa “Técnicas de animación a la lectura”, para mejorar la Comprensión Lectora en estudiantes del quinto grado de Primaria de la Institución Educativa N° 81007 “Modelo”-Trujillo, 2016 - Reyna Burgos, Rocío Rosmery (2017)
The main objective of this research was to verify that the Program "Techniques of animation to the reading" influences significantly in the improvement of the reading comprehension. The study was carried out with a sample of 31 students of the fifth grade of primary of the Educational Institution. n ° 81007 "Model" -of Trujillo- 2016. The type of applied research was used, using the quasi-perimetal design. As a data collection instrument we used a test questionnaire called "Check What We Learned". The results allow us to confirm that the students of the experimental group have improved significantly in reading comprehension, this is due to their participation in the learning sessions of the program . In conclusion, the application of the "Reading Animation Techniques" Program to improve reading comprehension has significantly influenced the development of reading comprehension levels (literal, inferential, critical).